EUPHEMISM STUDY IN CONDOLENCES TWEETS BY INTERNATIONAL FC TOWARDS THE KANJURUHAN TRAGEDY - Nabila Aulia Stevanova Susanti; Emy Sudarwati (Jurnal Kata, 2024)
This study examines the use of euphemisms in tweets posted by international football clubs in response to the Kanjuruhan Stadium tragedy. Guided by Allan and Burridge's (2012) theory, fifteen tweets were analyzed and classified based on the types of euphemisms employed. The research identifies various euphemisms, including hyperboles, distortions, and metaphors, used to soften the impact of tragic events and convey condolences. Through a thorough analysis, the study explores the purposes of euphemisms in online communication and their effectiveness in conveying emotions while maintaining a respectful tone. The research also considers the influence of social media platforms on language variation and expression, highlighting Twitter's role as a platform for emotional expression. Furthermore, the study provides insights into communication dynamics in online spaces. It suggests avenues for future research to explore euphemism topics using alternative theoretical frameworks and sources beyond social media platforms. Overall, this research contributes to understanding how euphemistic language is utilized in digital discourse and its implications for online communication strategies.